Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^3-x^2-5x+125\)
\(=\left(x+5\right)\left(x^2-5x+25\right)-x\left(x+5\right)\)
\(=\left(x+5\right)\left(x^2-5x+25-x\right)\)
\(=\left(x+5\right)\left(x^2-6x+25\right)\)
\(x^6-x^4-9x^3+9x^2\)
\(=x^4\left(x^2-1\right)-9x^2\left(x-1\right)\)
\(=x^4\left(x-1\right)\left(x+1\right)-9x^2\left(x-1\right)\)
\(=x^2\left(x-1\right)\left[x^2\left(x+1\right)-9\right]\)
\(=x^2\left(x-1\right)\left(x^3+x^2-9\right)\)
\(x^4-4x^3+8x^2-16x+16\)
\(=\left(x^2+4\right)^2-4x\left(x^2+4\right)\)
\(=\left(x^2+4\right)\left(x^2+4-4x\right)\)
\(=\left(x^2+4\right)\left(x-2\right)^2\)
\(3a^2-6ab+3b^2-12c^2\)
\(=3\left(a^2-2ab+b^2-4c^2\right)\)
\(=3\left[\left(a-b\right)^2-\left(2c\right)^2\right]\)
\(=3\left(a-b+2c\right)\left(a-b-2c\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a/ \(x^3-5x^2+8x-4\)
= \(\left(x^3-x^2\right)-\left(4x^2-4x\right)+\left(4x-4\right)\)
= \(x^2\left(x-1\right)-4x\left(x-1\right)+4\left(x-1\right)\)
= \(\left(x-1\right)\left(x^2-4x+4\right)\)
= \(\left(x-1\right)\left(x-2\right)^2\)
b/ \(x^3-x^2+x-1\)
= \(\left(x^3-x^2\right)+\left(x-1\right)\)
= \(x^2\left(x-1\right)+\left(x-1\right)\)
= \(\left(x-1\right)\left(x^2+1\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 3x2 - 7x + 2
= 3x2 - 6x - x + 2
= (3x2 - 6x) - (x - 2)
= 3x (x - 2) - (x - 2)
= (3x - 1) (x - 2)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(2x^2-5x-12\)
\(=2x^2-8x+3x-12\)
\(=2x\left(x-4\right)+3\left(x-4\right)\)
\(=\left(x-4\right)\left(2x+3\right)\)
b) \(x^3+5x^2+8x+4\)
\(=\left(x^3+3x^2+2x\right)+\left(2x^2+6x+4\right)\)
\(=x\left(x^2+3x+2\right)+2\left(x^2+3x+2\right)\)
\(=\left(x^2+3x+2\right)\left(x+2\right)\)
\(=\left(x^2+x+2x+2\right)\left(x+2\right)\)
\(=\left[x\left(x+1\right)+2\left(x+1\right)\right]\left(x+2\right)\)
\(=\left(x+1\right)\left(x+2\right)\left(x+2\right)\)
\(=\left(x+1\right)\left(x+2\right)^2\)
c) \(x^4+x^2+1\)
\(=\left(x^4-x^3+x^2\right)+\left(x^3-x^2+x\right)+\left(x^2-x+1\right)\)
\(=x^2\left(x^2-x+1\right)+x\left(x^2-x+1\right)+\left(x^2-x+1\right)\)
\(=\left(x^2-x+1\right)\left(x^2+x+1\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(=6x^3-12x^2+x^2-2x+x-2\)
\(=\left(x-2\right)\left(6x^2+x+1\right)\)
b: \(=3x^4+3x^3-x^3-x^2-7x^2-7x+5x+5\)
\(=\left(x+1\right)\left(3x^3-x^2-7x+5\right)\)
\(=\left(x+1\right)\left(3x^3-3x^2+2x^2-2x-5x+5\right)\)
\(=\left(x+1\right)\left(x-1\right)\left(3x^2+2x-5\right)\)
\(=\left(x-1\right)^2\cdot\left(x+1\right)\left(3x+5\right)\)
c: \(=4x^3+x^2+4x^2+x+4x+1\)
\(=\left(4x+1\right)\left(x^2+x+1\right)\)
a) 5x(x - 2) - 32(x -2) = (5x - 9)(x - 2)
b) 16x2 - (x2 + 4)2 = (4x - x2 - 4)(4x + x2 + 4) = -(x - 2)2(x + 2)2
c) 5x2 - 5xy + 7y7x = 5x2 - 5xy + 49xy = 5x2 + 44xy = x(5x + 44y)
d) 3x2 - 8x + 4 = 3x2 - 6x - 2x + 4 = 3x(x - 2) - 2(x - 2) = (3x - 2)(x - 2)
e) x4 + 64 = x4 + 16x2 + 64 - 16x2 = (x2 + 8)2 - 16x2
= (x2 + 8 - 4x)(x2 + 8 + 4x)